Comprehensive sizing process, actuation mechanism selection, and development of Gannet-inspired amphibious drones - Pena, I.; Billingsley, E.; Zimmerman, S.; Vasconcellos, R.; Abdelkefi, A. [UNESP]; AIAA (Amer Inst Aeronautics & Astronautics, 2020)
A drone capable of not only traveling through both air and water, but also able to transition between the two mediums provides many applications. Ranging from data collection in harsh environments to espionage in hostile territories. A drone which also mimics the appearance of an avian species found in nature could achieve these missions by blending in with its surroundings to avoid being identified as a foreign object. Because bioinspired flying, diving, and swimming drones are complex in design, this study limits the analysis to airfoil performance, buoyancy control, and a proposed propulsion mechanism design. Two-dimensional aerodynamic analysis is performed over an airfoil inspired by the albatross and other known NACA airfoils to compare the expected performance of each. The same airfoils are then analyzed in three dimensions by comparing a wing shape inspired by the gannet to common wing shapes seen in industry today. Features of the drone are also designed to mimic those of a gannet, a species efficient with traveling and transitioning between mediums while in search of prey. These features include a gannet-shaped head to aid in smooth water-entry, and an actuation mechanism to transition from flight mode (wings extended) to diving mode (wings fold along the fuselage).